Isolation of the operative field on the basis of contemporary reports and own observations - Chałas, Renata; Wójcik-Chęcińska, Ilona; Kamińska-Pikiewicz, Katarzyna; Łój-Maczulska, Agnieszka; Maksymiuk, Paweł (Journal of Stomatology, 2016)
Introduction. One of the conditions of an aseptic procedure during dental treatment is the isolation of the operative field against saliva access. Properly placed rubber dam proves most effective in maintaining dryness over the treated tooth. Despite significant advantages of using a rubber dam, as well as the introduction of new products and improvements to the existing ones, still a large number of practitioners around the world have not implemented it into their daily practice. Aim of the study. To assess the use of a rubber dam on the basis of prepared survey, and to broaden awareness of dentists on its use. Materials and methods. OptiDam was used during different treatments, both preventive and endodontic, in 98 patients, including 65 women and 33 men aged 18-71 years. The procedure was evaluated on the basis of the prepared survey and the results were analyzed using descriptive statistics and presented in tables. Results. OptiDam was generally assessed by dentists as very good and good. Top rated were the steps for rubber dam preparation outside the patient’s oral cavity i.e. ease of puncturing holes in the rubber dam and ease in mounting the three-dimensional rubber dam on a frame. The whole procedure of placing the rubber dam took the dentists an average of 1-5 minutes in nearly 43% of cases. Overall rating of a rubber dam (“anterior” and “posterior”) was good or very good in 90% of comments. Patients questioned about the comfort of treatment after the placement of OptiDam, assessed it positively. Conclusions. The research showed that OptiDam fulfills practitioners’ expectations regarding tight working field isolation during dental treatment. High percentage of doctors who have already used a 3-D rubber dam is an indicator of growing interest in this method of the operative field isolation.